2013
DOI: 10.15376/biores.8.4.5202-5218
|View full text |Cite
|
Sign up to set email alerts
|

Pressurized Hot Water Flow-through Extraction of Birch Sawdust with Acetate pH Buffer

Abstract: Birch sawdust was extracted with a pressurized hot water (PHW) flowthrough system. The pH of the extract was controlled during extraction by the addition of acetic acid/sodium acetate buffer. Three different pH levels, 4.0, 4.2, and 4.6, were used. Extraction temperatures were 160, 170, and 180 °C, with a constant 4 mL/min flow rate through the 50 mL extraction vessel. During PHW extraction with plain water, the end pH of the extract dropped from 5 to below 3. Buffers kept the pH of the extracts constant durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Chemical composition, solid recovery, and component removal of switchgrass before and after pretreatment with ionic liquid-water mixtures are summarized in Table 1 20 and thus reduced the extent of xylan solubilization from "auto-hydrolysis" effects, as indicated by the nearly neutral pH of the biomass liquor generated (Table 1).…”
Section: Compositional Changesmentioning
confidence: 99%
“…Chemical composition, solid recovery, and component removal of switchgrass before and after pretreatment with ionic liquid-water mixtures are summarized in Table 1 20 and thus reduced the extent of xylan solubilization from "auto-hydrolysis" effects, as indicated by the nearly neutral pH of the biomass liquor generated (Table 1).…”
Section: Compositional Changesmentioning
confidence: 99%
“…Extracted AcGGM from Norway spruce ( Picea abies ) was provided by the Finnish Forest Research Institute (Metla). The extraction conditions were studied and optimized in a previous study for by researchers at the Finnish Forest Research Institute (Metla), and AcGGM was obtained as a solution with a concentration of 30 wt %. To remove impurities and to narrow down the molar mass distribution [low polydispersity (PDI)], the extract was purified.…”
Section: Methodsmentioning
confidence: 99%
“…It was also found that the degradation of hemicellulose chains could somewhat be reduced, but then the hemicellulose yield decreased. Both Song et al (2011a,b) and Kilpeläinen et al (2013) found an optimum of extraction pH around 4 regarding high molar-mass and yield. Since the optimal extraction pH seems to be a rather narrow interval a more precise controlling method is highly needed.…”
Section: Introductionmentioning
confidence: 94%
“…Their results showed that the molar mass of the extracted hemicelluloses could be preserved to some extent with this passive pH control, but at the expense of the total hemicellulose yield (Song et al, 2011a,b). Another attempt to control pH during hot-water extraction was made with a flow-through extraction system and sodium acetate/acetic acid buffer (Kilpeläinen et al, 2013). It was also found that the degradation of hemicellulose chains could somewhat be reduced, but then the hemicellulose yield decreased.…”
Section: Introductionmentioning
confidence: 99%